INTEGRITY, DIGNITY AND THE ACT RESPECTING INDUSTRIAL ACCIDENTS AND OCCUPATIONAL DISEASES: CAN THE ACT PROVIDE MORE APPROPRIATE COMPENSATION FOR SEXUAL HARASSMENT VICTIMS? - Jacobs, Laverne (Revue de droit de l'Université de Sherbrooke, 2000)
The plight of victims of workplace sexual harassment in Quebec has become a matter of great concern in recent years. The worker who receives compensation through the Commission de la santé et de la sécurité du travail (CSST) for an injury resulting from the sexual harassment finds herself with no recourse to the Quebec Charter for moral, material or exemplary damages. This principle has become entrenched in the law since the decision of Béliveau St-Jacques v. Fédération des employées et employés de services publics inc. [1996] 2 S.C.R. 345.The matter is further complicated by the fact that the Act respecting industrial accidents and occupational diseases compensates only for loss of integrity, providing a completely inappropriate compensation for sexual harassment – an incident through which the person’s dignity is first and foremost put under attack. In this paper, the author explores the possibility of reforming the Act in order to provide a more appropriate compensation for victims of workplace sexual harassment, one that addresses the very real affront to dignity that sexual harassment poses. As the Act is grounded in a particular social and legal history, this exploration involves a review of its history and evolution as well as an examination of recent decisions by the CSST’s reviewing bodies. Consideration of the place of the person in Quebec Civil Law and the definition of certain personality rights (integrity and dignity) also form an integral part of this paper.